2011
DOI: 10.1155/2011/986021
|View full text |Cite
|
Sign up to set email alerts
|

Process-Parameter-Dependent Structural, Electrical, and Optical Properties of Reactive Magnetron Sputtered Ag-Cu-O Films

Abstract: Silver-copper-oxide thin films were formed by RF magnetron sputtering technique using Ag80Cu20target at various oxygen partial pressures in the range 5 × 10−3–8 ×10−2 Pa and substrate temperatures in the range 303–523 K. The effect of oxygen partial pressure and substrate temperature on the structure and surface morphology and electrical and optical properties of the films were studied. The Ag-Cu-O films formed at room temperature (303 K) and at low oxygen partial pressure of 5 × 10−3 Pa were mixed phase of Ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(34 reference statements)
1
2
0
Order By: Relevance
“…The absorption peak observed at 490 cm −1 for the Ag=CuO film with a 100 nm Ag thickness was related to the infrared active Ag-O mode for the Ag 2 O phase. 29) The results of FTIR confirmed the results of XRD analysis.…”
Section: Ftir Analysissupporting
confidence: 72%
“…The absorption peak observed at 490 cm −1 for the Ag=CuO film with a 100 nm Ag thickness was related to the infrared active Ag-O mode for the Ag 2 O phase. 29) The results of FTIR confirmed the results of XRD analysis.…”
Section: Ftir Analysissupporting
confidence: 72%
“…The Ag–C thin film was distinctly observed for all electrocatalysts at 2θ = 39.6° . During the first 15–75 min of reduction, the crystal structures of oxide species were visible, including AgO x , ,, CuO x , ,,, and Ag x Cu y O z . , The oxide formation was probably covered by Ag after 140 min of reduction, as seen by the apparent Ag plane of Ag(111), Ag(200), and Ag (220).…”
Section: Resultsmentioning
confidence: 99%
“…Uthanna et al [9] have reported the eect of deposition temperature on the structural, electrical and optical properties of AgCuO * corresponding author; e-mail: eevan2003@yahoo.co.in; elam@fct.unl.pt lms RF magnetron sputtered using the Ag 70 Cu 30 target. Narayana Reddy et al [10] have studied the effect of oxygen partial pressure and substrate temperature (T s ) on the structural, electrical and optical properties of AgCuO lms deposited using Ag 80 Cu 20 target. In this investigation, thin lms of Ag 2 Cu 2 O 3 were deposited by RF magnetron sputtering of Ag 50 Cu 50 target at dierent T s and studied the eect of T s on the core level binding energies, crystal structure, surface morphology and electrical properties.…”
Section: Introductionmentioning
confidence: 99%